The Lost Love Song - Darke, Minnie (London : Transworld Digital, 2020)
A feel-good romance by the author of Star-crossed, perfect for anyone who loves David Nicholls, Marian Keyes and Jojo Moyes
Keywords: Romance; Modern and contemporary fiction; Romance fiction